2008
DOI: 10.3168/jds.2007-0761
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary Infusion of Leptin Decreases Proliferation of Mammary Epithelial Cells in Prepubertal Heifers

Abstract: High energy intake and excessive body fatness impair mammogenesis in prepubertal ruminants. High energy intake and excessive fatness also increase serum leptin. Our objective was to determine if an infusion of leptin decreases proliferation of mammary epithelial cells of prepubertal heifers in vivo. Ovine leptin at 100 microg/ quarter per d with or without 10 microg of insulin-like growth factor (IGF)-I was infused via the teat canal into mammary glands of prepubertal dairy heifers; contralateral quarters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
(48 reference statements)
1
17
1
6
Order By: Relevance
“…The percent decrease of lactose, however, is relatively small (Pyörälä 2003), and that was not affected by S. aureus subclinical infection during the present study. Given the expected differences of milk production (Natzke et al 1965) between front and rear quarters and the significant differences already reported on milk constituents between healthy and unhealthy ones (Nielsen et al 2005), it was essential that the statistical model adopted (Silva et al 2008) consider such fixed factors of variations. S. aureus IMI had markedly affected the SCC of both front and rear infected quarters, but tissue damage seemed to be more evident in front quarters than in rear ones, and that could be partially explained by a dilution effect due to the normal 40:60 milk production ratio between them (Natzke et al 1965), which may have accounted for the S*H interaction observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The percent decrease of lactose, however, is relatively small (Pyörälä 2003), and that was not affected by S. aureus subclinical infection during the present study. Given the expected differences of milk production (Natzke et al 1965) between front and rear quarters and the significant differences already reported on milk constituents between healthy and unhealthy ones (Nielsen et al 2005), it was essential that the statistical model adopted (Silva et al 2008) consider such fixed factors of variations. S. aureus IMI had markedly affected the SCC of both front and rear infected quarters, but tissue damage seemed to be more evident in front quarters than in rear ones, and that could be partially explained by a dilution effect due to the normal 40:60 milk production ratio between them (Natzke et al 1965), which may have accounted for the S*H interaction observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, they found that larger leptin doses were needed when the media was supplemented with IGF-1. Silva et al (2008) infused recombinant ovine leptin and IGF-1 for 7 days into separate quarters of prepubertal heifers fed to gain at 700 g/day, but retaining normal mammary development. The IGF-1 dose (10 mg/quarter per day) had previously raised epithelial cell proliferation by , 50% (Silva et al, 2005) while the leptin dose (100 mg/qtr per day) ensured supraphysiological leptin levels in the parenchyma (higher by , 25 3 than with placebo).…”
Section: Leptin and Mammary Development And Functionmentioning
confidence: 99%
“…That number can be changed by different factors (such as nutrition (Silva et al, 2008), health (Wagner et al, 2009), and heat stress (Collier et al, 2006). Changes in management that occur during lactation and even before the onset of lactation (dry period) can modify milk production.…”
Section: Introductionmentioning
confidence: 99%